Goethe's modernisms - Tantillo, Astrida Orle (Continuum, 2010)
Goethe's Modernisms demonstrates Goethe's pivotal influence on the development of Western society. It also reveals him to be one of modernity's profoundest critics. His influence has not only shaped aesthetic issues, but a myriad of cultural and intellectual ones as well. By studying his works, we can thus gain insights into the foundational principles of modern society and its shortcomings. Tantillo explores Goethe's role within the culture wars that have been with us for some time, his role as a both a progenitor and a critic of modernity, and suggests how we might rethink aspects of our cur.